ANALISIS PENGARUH PERSEPSI KONSUMEN TERHADAP EKSISTENSI PASAR TRADISIONAL DI KOTA PONTIANAK - B611109001, DIAH LAKSMINI NOOR (Jurnal Ekonomi Daerah (JEDA), 2019)
The existence of traditional markets remains a part of the rapid development of urban society.Thesis research aims to determine the effect: 1) Perception of consumer purchasing decisionsagainst the existence of traditional markets 2) consumer perceptions about the role of government instructuring and managing traditional markets to the existence of traditionalmarkets 3) Perceptions of consumer purchasing decisionsand consumer perceptions of the role of government in managing and managing traditional markets for the existence of traditional markets.          The results showed that consumer purchasing decisions that have a significant influence on the existence of traditional markets in Pontianak City with information coefficient value (r) of 0.554 and t count of 12.398 Consumer perception in the context of traditional management and management has a significant influence on the existence of traditional markets in Pontianak City from the average value (r) of 0.516 and t count of 11.207. While the number of people involved in the traditional arrangement and smoothing of traditional existence with effectiveness of 17.8%. Perception of consumer purchasing result and consumer perception in structuring and management of traditional market very significant to existence of traditional market in Pontianak with R value equal to 0,637 with F count equal to 117,583. As for R² (coefficient of determination) Looking at 0.405. The amount of effective contribution from the two variables in this study is 40.5% of which the decision variable purchase decision of 22.7% and the perception of the government role of 17.8% while the remaining 59.5% by other factors that are not available in research this. Keywords: Perception, Existence, Traditional Market, Comsumer